Coefficient bounds for a certain subclass of close-to-convex functions associated with the koebe function / Sidik Rathi, Shaharuddin Cik Soh and Ajab Akbarally - Rathi, Sidik; Cik Soh, Shaharuddin; Akbarally, Ajab (Universiti Teknologi MARA Press (Penerbit UiTM), 2018)
We consider here the functions...